Immobilisation of phanerochaete chrysosporium in PVA-Alginate-sulphate beads for decolourization of textile effluents - Ahmad Nasir, Nor Atikah Husna (2013)
Textiles industry is one of the main sources that contribute to water pollution due to the release of substances such as wax, surfactant and dyes into water bodies. Until now, many methods for textile effluents treatments were introduced. Unfortunately, most of them are expensive and ineffective. Recently, the ability of microorganisms as an alternative to overcome these problems has attracted attentions. In this study, textile effluents were treated with immobilised the white-rot fungi, Phanerochaete chrysosporium cells in PVA-alginate-sulphate beads. Optimisation conducted using Design Expert 6.0.4 software. A two level factorial with three factors programme was used for the optimisation. The efficiency of this system was determined by several tests such as colour and COD reduction, enzymatic activities, reusability, storage stability and toxicity test. Results showed that the optimum colour reduction and enzyme activity was achieved at 37 ºC, 10 g of immobilised cells and 300 mg/L dyes concentration. At the optimum condition, immobilised cells were able to decolourize dyes and reduced COD content up to 50% and 33% higher compared to free cells. Meanwhile, the enzyme activity of immobilised cells was doubled as compared to free cells. The suggested model equation are significant since the predicted and actual value show percentage of error less than 5% for colour, COD reduction and enzymatic activity. Reusability test showed the immobilised cells could be reused up to four times to treat dyes effluents. For the stability test, the ability of immobilised cells to reduce dyes effluents decreased to about 10% after two-month storage as compared to free cells which decreased to about 25%. Toxicity test proved that immobilised cells could reduced the toxicity level up to 4% higher than free cells. In conclusion, P.chrysosporium was successfully immobilised in PVA-alginate-sulphate beads and could serve as a potential method for dyes effluents treatment.